PharmaX - Saif Shayeb; Osama Ishtaiwi (My University, 2025)
This report documents the design and implementation of PharmaX, a compact automated pharmacy dispensing system built around a three-axis cartesian gantry, dual ultrasonic verification (pre-pull and post-pull), and a dual-interface HMI (web UI and keypad+LCD). The motion layer (Arduino Mega) uses trapezoidal velocity profiles, homing via limit switches, software limits, and a bounded retry policy to increase reliability. Two ESP32 modules provide a Wi-Fi SoftAP web ordering interface and a local keypad/LCD interface. The system retrieves medication boxes from a fixed 3 × 4 shelf grid and delivers them via a servo-assisted ramp to a user bin. We detail theoretical background, related work, methodology, results, and recommendations. The prototype demonstrates high success rates and reduced handling time, validating deterministic, low-cost pharmacy automation.